IMPROVING READING COMPREHENSION ABILITY OF THE 2ND SEMESTER OF PUBLISHING STUDENTS AT POLITEKNIK NEGERI MEDIA KREATIF THROUGH COLLABORATIVE STRATEGIC READING TECHNIQUE APPLICATION - Liza Amalia Putri; Refi Yuliana (Jurnal Ilmiah Publipreneur, 2021)
This research analyzed Collaborative Strategic Reading (CSR) in improving the reading comprehension ability of the 2nd semester Publishing students at Politeknik Negeri Media Kreatif and the difficulties found in applying the CSR technique in improving reading comprehension ability. The aims of this research were to find out if CSR strategy improved the student's reading comprehension ability and to find out the difficulties found in applying CSR strategy in improving the reading comprehension ability. The methodology used in this research was Classroom Action Research (CAR). The data of this research were the result of reading tests. The subjects of the research were forty-four students of the second semester of Publishing study program at Politeknik Negeri Media Kreatif. The findings of the research showed that the mean of pre-test was 54,3 and the mean of post-test was 70,2. Based on the findings and the analysis of the data above, it was concluded that using CSR improved the students reading comprehension.